Cyber fraud: determinants that drive TM Info Media Sdn Bhd towards brand protection / Nazly Mahyunni Mohamad Suhof and Nor Akhmal Hakim Kasmani - Mohamad Suhof, Nazly Mahyunni; Kasmani, Nor Akhmal Hakim (Faculty of Business and Management, 2013)
Internet has been the in-thing in Malaysia these recent years, regardless of the benefits that the internet brings often overshadow the threats that tag along. In this globalize era, not only individuals were exposed to the internet threats but also business firm. This study will emphasize on the determinants that derive TM Info Media Sdn Bhd towards brand protection. Due to the insufficient business and marketing literature, researchers have to dig deeper into the journal of information science, computer security and legal protection to provide reader with the theories and understandings towards the technical terms involved in this study. The researcher hope with this research will help in providing insight about the current legal protection and threats that firm may involves in, throughout this paper researcher will found evidence show that if the Brand is not protected hence it will be destructive and cause not only financial injuries but also tarnish business firm name,